Female genital mutilation in the UK- where are we, where do we go next? Involving communities in setting the research agenda - Dixon, S; Agha, K; Ali, F; El-Hindi, L; Kelly, B; Locock, L; Otoo-Oyortey, N; Penny, S; Plugge, E; Hinton, L (BioMed Central, 2018)
Background Female Genital Mutilation (FGM) is all practices involving cutting, alteration or injury to the female genitalia for non-medical reasons. It is a form of violence against women and children, with no benefits and many harms. In 2014, the UK Government committed to working to eliminate FGM. Steps taken towards this aim included creation of educational and safeguarding resources for professionals, and legislative changes including a mandatory reporting duty for professionals in England and Wales (where if a girl under 18 discloses or is found on examination to have FGM then the professional is mandated to report this to the police), and an FGM Enhanced Dataset applicable to NHS organisations in England requiring the submission of personal data about women and girls who have had FGM to NHS Digital. To date, compliance with dataset returns from primary care services have been low. This report describes using patient and public involvement (PPI) to identify research and service priorities to support communities affected by FGM. Methods We held a series of PPI events (4 focus groups, and a multi-agency seminar) in 2015–2016, following the introduction of these legislative changes, speaking to community members, and professionals involved in their care. We asked participants to consider what they identified as research, knowledge and service priorities to support communities affected by FGM. Results The impact of these legislative and reporting requirements on the trust needed for community members to seek to consult health services was identified as important for further research. Priorities for service development were holistic services, that met a woman’s needs throughout her lifecourse. Participants emphasised the importance of understanding how to listen, involve and utilise community voices in developing education for professionals, designing services, and developing policy. Conclusions There was a desire for change to develop from within affected communities; any learning and resources need to be co-created and constructed in such a way that they can be effectively shared between women, communities, and professionals. Questions remain about how to define community consultation, how to recognise when it was adequate, and how to hear beyond community activists to hear a wider range of voices.